ANEMIA PADA POST PARTUM - Afria, Rahmi; Harni Susilawati, Enung; Fauzia, Fauzia (Jurnal Kesehatan Siliwangi, 2024)
Anemia is a complication that is postpartum mothers. The main cause is bleeding during the birth process. In 2023, 92 (8.47%) of the 1085 mothers who gave birth spontaneously will handle post-partum hemorrhage at the Sekarwangi Hospital. The aim of this midwifery care is to apply Post Partum Midwifery Care to Mrs. W aged 30 years P3A1 with moderate anemia at Sekarwangi Hospital.The method in preparing this assignment report is a case study. The form of documentation is SOAP. Data collection techniques obtained through interviews, physical and laboratory examination observations, the mother gave birth to her fourth child 8 hours ago, the mother had a miscarriage once, the mother complained of feeling weak, dizzy, her eyes were dizzy. Examination of vital signs showed blood pressure 90/60 mmHg, pulse 92x/m, respiration 21x/m, temperature 36.5 C, face, conjunctiva and gums pale, genital examination found blood output 50cc, and supporting examination with hemoglobin examination with results of 7.7 gr/dl. The analysis that can be confirmed is "Mrs. W, 30 years old P3A1 post partum 8 hours with moderate anemia." The management carried oral therapy, amoxicillin and Fe tablets, blood transfusions, observing the general condition, bleeding, uterine contractions, nutritional counseling. Conclusion from midwifery care for moderate anemia is that it can be carried out well with cooperation between the client and the author. be able to carry out the recommendations suggested by the midwife, from that the midwife is expected treat anemia in appropriate service standards and midwife authority.